PENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK SOSIODRAMA UNTUK MENGURANGI PERILAKU PROKRASTINASI AKADEMIK SISWA DIKELAS X SMK NEGERI 1 PERBAUNGAN - Br Hasibuan, Khoirunnisa; Utami Lubis, Widya (PGSD UMN Al-Washliyah, 2023)
This research aims to determine the effect of group guidance services using sociodrama techniques to reduce the academic procrastination behavior of students in class X of SMK Negeri 1 Perbaungan. This research is experimental research because this research seeks to determine the influence of the role of group guidance services using sociodrama techniques to reduce the academic procrastination behavior of students in class X of SMK Negeri 1 Perbaungan. This research is experimental research because this research seeks to determine the influence of the role of group guidance services using sociodrama techniques to reduce the academic procrastination behavior of students in class X of SMK Negeri 1 Perbaungan. The research population was all students of class X of SMK Negeri 1 Perbaungan, totaling 36 students. The research sample was students of class pretest 43% and posttest 79.1% and the difference in improvement obtained was 36.1% and pretest 63.2% and posttest 65.9%, the difference in improvement obtained was 28%. Both of them experienced a higher increase, namely 36.1% compared to the pretest which only obtained a score of 28%. Thus, the conclusion is that the procrastination attitude of students at Perbaungan State Vocational School, the procrastination attitude of students at Perbaungan State Vocational School 1 experienced changes after being provided with group counseling services using sociodrama techniques.